Regarding the Practical Guide Updating for the Treatment of Acute Pericarditis in Cienfuegos - René Mick Cabrera Núñez (Revista Finlay)
The clinical practice guidelines aim at gathering and evaluating all relevant evidence available at the time of writing. They deal with a specific topic to help doctors select the best possible treatment strategy for a particular patient, who suffers a certain disease, not only taking into account the final result, but also weighing the risks and benefits of a diagnostic procedure or specific therapeutic. For these reasons, the clinical practice guide for the treatment of acute pericarditis, which was reviewed and endorsed by the specialists, has recently been updated in the Cardiology Department of the Dr. Gustavo Aldereguía Lima University General Hospital in Cienfuegos.